Spatial variability of cultural landscape vulnerability and influential factors in ethnic villages of Southeast Guizhou - Chong Wu; Mengling Yang; Haidong Wei; Lei Gong; Guowei Tan (Scientific Reports)
Abstract In Southeast Guizhou, a region of China rich in ethnic diversity, the cultural landscapes of ethnic villages are increasingly vulnerable under the pressures of urbanization and tourism development. This study assesses the vulnerability of 43 ethnic villages in Leishan County using the Vulnerability Scoring Diagram (VSD) model, which evaluates exposure, sensitivity, and coping ability. Analyses using spatial autocorrelation and geographic weighted regression reveal distinct spatial patterns of vulnerability, with the northern region exhibiting higher vulnerability indices than the southern region. The study identifies tourism development, protection policies, and financial investments as primary influencing factors of vulnerability, with varying degrees of impact across different geographical areas. The findings provide a robust framework for assessing and visualizing the vulnerability of cultural landscapes in ethnic villages, guiding the development of tailored protection strategies to mitigate risks and preserve cultural heritage.